The relationship between corporate social responsibility and firm financial performance, and the corporate culture traits associated with corporate social responsibility, in the context of South Africa - Swanepoel, Samantha (University of Pretoria, 2023)
Mini Dissertation (MPhil (Corporate Strategy))--University of Pretoria, 2022.